Introductory accounting - Ringstrom, David H.; Perry, Gail A. (Idiot's guides., 2016)
Accurate accounting is the key to a successful business. But when you're dealing with assets and liabilities, profit and loss, and debits and credits, juggling all the numbers can quickly get confusing. Idiot's Guides: Introductory Accounting gives you everything you need to know about basic financial accounting to manage your dollars and cents and keep your accounts in order. Ideal for small businesses, as well as any large company bookkeeper, this book covers: *Structuring your business and choosing an accounting method *Setting up an accounting system and basic operating procedures (tracking sales, determining costs, managing cash, etc.) *Creating employee records, maintaining a payroll system, and accounting for benefits * Keeping tax and benefit records * Reporting costs * Closing out cash journals and employee accounts at month end and balancing ledgers *Preparing month-end and year-end statements and reports *Producing a balance sheet and monthly profit-and-loss (P&L) statements *Using accounting software.